Evaluation the enzyme inhibitory properties of Commandaria grape pomace extracts associated with hyperglycemia - Goulas, Vlasios (My University, 2022)
The grape pomace contains plethora of polyphenols as phenolic acids, flavanoids, anthocyanins, tannins and stilbenes, which are linked with diverse health effects. Many studies manifest that grape phenolics exert potent anti-hyperglycemic effects. The α-amylase and α-glucosidase inhibitory effects are considered as a possible mechanism of their action. Commandaria is a dessert wine, which is produced by wine-making sun-dried grapes. Thus, its pomace comprises high concentration of polyphenols due to dehydration. The objective of this work was to evaluate grape pomace phenolics as potential enzyme inhibitors related with hyperglycemia. Therefore, the effect of extraction systems (methanol 100%, methanol-water 80 – 20%, methanol-water 60 – 40%, ethanol 100%, ethanol-water 80 – 20%, ethanol-water 60 – 40%, acetone, acetone-water 80 – 20%, and acetone-water 60 – 40%) on the bioactive composition and enzyme inhibitory properties was studied. Results demonstrated that ethanolic and hydroethanolic grape pomace extracts had the highest phenolic and hydroxycinnamate contents followed by methanolic and hydromethanolic extracts. Acetone and its aqueous mixtures also recover higher amounts of flavanols compared to alcohols. Furthermore, results showed the α-amylase and α-glucosidase inhibitory activities of Commandaria grape pomace extracts were strongly affected by extraction system. The a-amylase and a-glucosidase inhibitory effects (IC50) ranged from 19.1 ± 0.8 to 27.6 ± 1.4 µg · mL−1 and from 70.4 ± 4.9 to 88.9 ± 6.7 µg · mL−1, respectively. The findings suggest the use of pure alcohols and methanol-water (80 – 20%) to prepare extracts with potent enzyme inhibitory activities. Overall, the current study highlights the Commandaria grape pomace as inhibitors of α-glucosidase and α-amylase and provides a knowledge-base for the selection of the most appropriate solvents to produce antihyperglycemic extracts.